Analysing politics and protest in digital popular culture : a multimodal introduction - Way, Lyndon (London : SAGE Publications Ltd, 2021)
"Gives students the tools they need to uncover for themselves the hidden politics of today's digital infotainment labyrinth." - Theo van Leeuwen, University of Southern Denmark and University of New South Wales. We now increasingly encounter and do politics not through news or broadcast media, but when we scroll through social media feeds, open apps, compose and like posts, and comment on or share videos. This book explores how to analyse politics and protest in the places we experience it most in our everyday lives - on our phones, tablets and laptops. It provides a hands-on analytical toolkit, showing you how to critically analyse language, image, video and audio in a way that reveals the discourses, ideologies and power that run through digital popular culture. From the authoritarianism of Donald Trump, to the protests of Gezi Park, to the campaigns of Extinction Rebellion, to angst against Brexit, Lyndon Way shows you how to analyse the politics in digital everyday life across media including: {u2022}{u2003}Online comments {u2022}{u2003}Memes {u2022}{u2003}GIFs and mash-ups {u2022}{u2003}Music videos {u2022}{u2003}Parodies and satire. It is an essential guide for students and researchers across media and communication, politics and discourse studies.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Popular culture -- Political aspects